Energy performances and numerical investigation of solid-state magnetocaloric materials used as refrigerant in an active magnetic regenerator. (June 2018) - Aprea, C.; Greco, A.; Maiorino, A.; Masselli, C.
Highlights: 2D model of an Active Magnetocaloric Regenerative refrigeration cycle. Experimental validation of the model with Rotary Permanent-Magnet Magnetic Refrigerator. The model constitutes an accurate tool to predict virtually the performance of RPMMR. Map of performances for gadolinium as benchmark solid-state refrigerant. Exploring the performance employing different magnetocaloric materials. Abstract: Magnetic is the most diffused, developed and evolved technique among solid-state cooling, a class of ecofriendly refrigeration systems employing solid-state caloric materials. Active Magnetic Regenerative refrigeration cycle (AMR), a Brayton based thermodynamical cycle, is the benchmark cycle for magnetic refrigeration. This paper aims to provide a map of energetic performances of an Active Magnetic Refrigerator by the development of a two-dimensional numerical model, whom replies the behaviour of one of the regenerators mounted in 8Mag, the experimental prototype of the first Italian Rotary Permanent Magnet Magnetic Refrigerator (RPMMR), mounting gadolinium. To this hope, through the model a performance map has been delineated and it has been investigated the behaviour of the AMR regenerator, mounting gadolinium, in order to explore the limit conditions of prototype working, in terms of cold-hot heat exchanger range, fluid flow rate and frequency. In a second step, the performance map has been extended to other MCE materials, possible candidates for magnetic refrigeration at room temperature.